1992
DOI: 10.1111/j.1530-0277.1992.tb00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Determined Differences in the Antagonistic Effect of Pressure on Ethanol‐Induced Loss of Righting Reflex in Mice

Abstract: Hyperbaric exposure antagonizes ethanol's behavioral effects in a wide variety of species. Recent studies indicating that there are genetically determined differences in the effects of body temperature manipulation on ethanol sensitivity suggested that genotype might also influence the effects of hyperbaric exposure on ethanol intoxication. To investigate this possibility, ethanol injected long sleep (LS)/Ibg (2.7 g/kg), short sleep (SS)/Ibg (4.8 g/kg), 129/J (2.9 g/kg), and C57BL/6J (3.6 g/kg) mice were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Subsequent experiments determined that the non‐specific excitatory effects attributed to pressures above 50 ATA could be eliminated by using lower levels of hyperbaric exposure. This work used pressures up to 12 ATA heliox to antagonize behavioral and biochemical effects of ethanol (Alkana and Malcolm 1981; Alkana et al . 1992; Bejanian et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent experiments determined that the non‐specific excitatory effects attributed to pressures above 50 ATA could be eliminated by using lower levels of hyperbaric exposure. This work used pressures up to 12 ATA heliox to antagonize behavioral and biochemical effects of ethanol (Alkana and Malcolm 1981; Alkana et al . 1992; Bejanian et al .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that exposure to 12 times normal atmospheric pressure (ATA) of helium‐oxygen gas (heliox) directly antagonizes the behavioral and biochemical actions of ethanol (Alkana and Malcolm 1981; Alkana et al . 1992; Bejanian et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DHβE doses (1.0 – 3.0 mg/kg) were based on published and unpublished studies from our lab that were within an effective range of doses for blocking the behavioral effects of nicotine (Damaj et al 1995, 2003). Ethanol doses (2.0 – 3.5 g/kg) were chosen based on active doses in previous studies (Alanka et al 1992, Browman et al 2000). …”
Section: Methodsmentioning
confidence: 99%
“…Studies show that exposure to 4–12 times normal atmospheric pressure (ATA) is a direct ethanol antagonist that blocks and reverses a broad spectrum of ethanol’s acute and chronic behavioral effects (Alkana and Malcolm, 1981;Alkana and Malcolm, 1982a;Malcolm and Alkana, 1982;Alkana et al , 1992;Nielsen et al , 1987;Bejanian et al , 1993;Davies et al , 1994;Davies et al , 1999;Davies and Alkana, 2001), as well as its effects at the biochemical (Davies and Alkana, 1998;Davies et al , 1999;Davies and Alkana, 2001) and molecular (Davies et al , 2003;Davies et al , 2004;Perkins et al , 2008) levels.…”
Section: Introductionmentioning
confidence: 99%